Histopathological Study of Host–Pathogen Interactions Between Cordyceps javanica PSUC002 and Hypothenemus hampei - Sinlapachai Senarat; Peerasak Bunsap; Pisit Poolprasert; Anjaree Inchan; Natthawut Charoenphon; Peerapon Sornying; Narit Thaochan (Journal of Fungi)
The use of entomopathogenic fungi (EPF), such as Cordyceps javanica, to reduce insect pest populations is gaining traction since it is an environmentally safe approach that can control many pests at different life stages. Here, we focus on the histopathology of the coffee berry borer, Hypothenemus hampei, infected by C. javanica. Morphological observation revealed that C. javanica conidia germinated within 12 h following inoculation according to light microscopic and ultrastructural levels. The fungus thoroughly penetrated the fat body and muscular tissue between 84 and 120 h post-inoculation. Transmission electron microscopy (TEM) confirmed the hyphal invasion of the cuticle at 12 h post-inoculation, with progressive tissue disruption and organelle degeneration, especially mitochondria and rough endoplasmic reticulum in adipocytes. All organelles were completely degenerated at 96 h post-inoculation. There was evidence of a connection between C. javanica activity and the coffee berry borer that might cause histopathological changes in the host defense against the pathogen, pointing to increased mortality and potential control of coffee berry borer in natural populations. Additionally, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) confirmed that apoptotic cells were slightly increased in the adipose tissue and integument of the coffee berry borer. The ability of C. javanica to fatally infect the coffee berry borer suggests that it could be deployed as a biological control agent in the field.